How Far Do Children Move? Spatial Distances after Leaving the Parental Home - Thomas Leopold; Ferdinand Geißler; Sebastian Pink (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Little is known about how far young adults move when they leave their parental home initially. We addressed this question using data from ten waves (2000 - 2009) of the German Socioeconomic Panel Study on spatial distances calculated by the geo-coordinates of residential moves (N = 1,425). Linear regression models predicted young adults· moving distance by factors at the individual, family, household, and community level. Overall, spatial distances of initial moveouts were strikingly small with a median value of only 9.5 kilometers. Those who were welleducated, female, single, childless, had highly educated fathers and high parental household incomes moved across greater distances. The effect of young adults· education was moderated by the local community·s degree of urbanization, supporting the brain drain assertion. In line with developmental models of migration, our results further show that young adults stayed closer if the parental household was still located at their place of childhood. We found two interactions with gender: At the family level, daughters stayed closer when leaving a single-parent household. At the community level, women from Eastern Germany moved farther, suggesting that the surplus of men in the Eastern periphery is at least to some extent an outcome of initial migration decisions.
Keywords: 330; Kinder; Erwachsene; Wohnstandort; Geographische Entfernung; Schätzung; Deutschland